Conservation Triage Falls Short Because Conservation Is Not Like Emergency Medicine - Vucetich, John A.; Nelson, Michael Paul; Bruskotter, Jeremy T. (Frontiers in Ecology and Evolution, 2017)
Similar to what, I believe, is the style of some of the articles in this special feature - our manuscript has no abstract